Revisiting the Role of Natural Killer Cells in Non-Alcoholic Fatty Liver Disease - Martínez-Chantar, María Luz; Delgado, Teresa C.; Beraza, Naiara (Frontiers in Immunology, 2021)
Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common form of chronic liver disease. The histological spectrum of NAFLD ranges from simple steatosis to chronic inflammation and liver fibrosis during Non-Alcoholic Steatohepatitis (NASH). The current view is that innate immune mechanisms represent a key element in supporting hepatic inflammation in NASH. Natural Killer (NK) cells are lymphoid cells and a component of the innate immune system known to be involved in NASH progression. Increasing evidence has shed light on the differential function of circulating and tissue-resident NK cells, as well as on the relevance of metabolism and the microenvironment in regulating their activity. Here, we revisit the complex role of NK cells as regulators of NASH progression as well as potential therapeutic approaches based on their modulation.